Good + Bad = ? Developmental Differences in Balancing Gains and Losses in Value‐Based Decisions From Memory. Issue 2 (15th January 2019) - Horn, Sebastian S.; Mata, Rui; Pachur, Thorsten
Abstract : Value‐based decisions often involve comparisons between benefits and costs that must be retrieved from memory. To investigate the development of value‐based decisions, 9‐ to 10‐year olds ( N = 30), 11‐ to 12‐year olds ( N = 30), and young adults ( N = 30) first learned to associate gain and loss magnitudes with symbols. In a subsequent decision task, participants rapidly evaluated objects that consisted of combinations of these symbols. All age groups achieved high decision performance and were sensitive to gain–loss magnitudes, suggesting that required core cognitive abilities are developed early. A cognitive‐modeling analysis of performance revealed that children were less efficient in object evaluation (drift rate) and had longer nondecision times than adults. Developmental differences, which emerged particularly for objects of high positive net value, were linked to mnemonic and numerical abilities.